2007
DOI: 10.4161/cc.6.19.4758
|View full text |Cite
|
Sign up to set email alerts
|

The NBS1-ATM Connection Revisited

Abstract: Nijmegen Breakage syndrome (NBS) is a rare autosomal recessive disorder characterized by microcephaly, immunodeficiency, and increased predisposition to the development of malignancy. 1,2 Due to the overlap of clinical and cellular features of patients with ataxia telangiectasia (AT), NBS was described as an AT variant syndrome until the underlying gene product mutation was identified. 3-5 Cells from both AT and NBS patients show increased sensitivity to ionizing radiation (IR), genomic instability and cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 64 publications
(124 reference statements)
2
42
0
1
Order By: Relevance
“…8) strongly supports the notion that the MRN complex is required for replication of the MVC genome ( Fig. 10) and that its role may be to recruit DNA repair factors to the replication center (14,37), as p-Nbs1 is essential to DSB repair (29). On the other hand, the MRN complex senses ATM activation, which in turn may mediate proteasome-dependent degradation of the MRN subunit (94) at later stages of infection.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…8) strongly supports the notion that the MRN complex is required for replication of the MVC genome ( Fig. 10) and that its role may be to recruit DNA repair factors to the replication center (14,37), as p-Nbs1 is essential to DSB repair (29). On the other hand, the MRN complex senses ATM activation, which in turn may mediate proteasome-dependent degradation of the MRN subunit (94) at later stages of infection.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, we found that in contrast to the results we obtained by silencing Mre11, knockdown of ATM reduced Nbs1 phosphorylation only slightly, indicating that a low level of activated ATM is sufficient to phosphorylate Nbs1. As Nbs1 is essential for DSB repair and genome stability (29), the persistent presence of p-Nbs1 in the MVC replication foci (Fig. 8A) suggests that this activated form may play a role in replication of the MVC genome.…”
Section: Vol 85 2011 Bocavirus Ddr Role In Dna Replication and Cellmentioning
confidence: 99%
“…Eukaryotic cells have developed two alternative DSB repair methods, direct ligation of the excised DNA ends (nonhomologous end joining, NHEJ) and homologous recombination (HR) (12)(13)(14)(15). DNA repair is stimulated by a phosphorylation-based signaling cascade, the DNA damage response (DDR) (16)(17)(18).…”
mentioning
confidence: 99%
“…Antibodies specific to phosphorylated ATM, pATM(S1981), and CHK2, pCHK2(T68), or CHK1, pCHK1(S345), were used as markers for ATM or ATR activation, respectively. NBS1 was also analyzed as it has been shown to be phosphorylated by ATM (5,44). Upon DOX incubation, phosphorylation of ATM and CHK1 was increased in the cell populations of tetON E1ϩE2 and tetON E1, although basal levels of the phosphorylated CHK1 appeared also higher in these cells (Fig.…”
Section: Hpv16 E1 Induces Activation Of Nf-b In Human Cervical Keratimentioning
confidence: 99%